15-Deoxy-Δ12, 14-prostaglandin J2 induced neurotoxicity via suppressing phosphoinositide 3-kinase. (February 2017) - Koma, Hiromi; Yamamoto, Yasuhiro; Nishii, Ayaka; Yagami, Tatsurou
Abstract: 15-Deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) induces neuronal cell death via apoptosis independently of its receptors. 15d-PGJ2 inhibits growth factor-induced cell proliferation of primary astrocytes via down-regulating phosphoinositide 3-kinase (PI3K)-Akt pathway. Although 15d-PGJ2 -reduced cell viability is accompanied with attenuation of the PI3K signaling in neuroblastoma, it has not been sufficiently clarified how 15d-PGJ2 induces cell death in primary neurons. Here, we found that 15d-PGJ2 exhibited neurotoxicity via inhibiting the PI3K signaling in the primary culture of rat cortical neurons. A PI3K inhibitor induced neuronal cell death regardless serum throughout maturation, confirming that PI3K is required for neuronal cell survival. The inhibitor disrupted neuronal cell bodies, shortened neurites thinly, damaged plasma membranes and activated caspase-3 similarly to 15d-PGJ2 . Little additive or synergistic neurotoxicity was detected between 15d-PGJ2 and the PI3K inhibitor. A PI3K activator prevented neurons from undergoing the 15d-PGJ2 -induced cell death in vitro . In vivo, the PI3K signaling is required for contextual memory retrieval, which was impaired by bilateral injection of 15d-PGJ2 into hippocampus. The activator suppressed the 15d-PGJ2 -impaired memory retrieval significantly. In neurons as well as primary astrocytes and neuroblastomas, 15d-PGJ2 exhibited cytotoxicity via suppressing the PI3K-Akt pathway in vivo and in vitro . Highlights: 15d-PGJ2 exhibited cytotoxicity via inhibiting the PI3K signaling in primary neurons. PI3K was required for neuronal survival throughout maturation regardless serum. PI3K activator prevented neurons from undergoing the 15d-PGJ2 -induced cell death. Injection of 15d-PGJ2 into hippocampus impaired contextual memory retrieval. PI3K activator suppressed the 15d-PGJ2 -impaired hippocampal memory retrieval.